2019
DOI: 10.1177/0960327119831067
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial role of vanillin, a polyphenolic flavoring agent, on maneb-induced oxidative stress, DNA damage, and liver histological changes in Swiss albino mice

Abstract: Vanillin, a widely used flavoring agent, has antimutagenic and antioxidant properties. The current study was performed to evaluate its beneficial role against hepatotoxicity induced by maneb, a dithiocarbamate fungicide. Mice were divided into four groups of six each: group 1, serving as negative controls which received by intraperitoneal way only distilled water, a solvent of maneb; group 2, received daily, by intraperitoneal way, maneb (30 mg kg−1 body weight (BW)); group 3, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…Our in vivo results from the mice model also reflect that Van treatment significantly alleviated the MPTP-induced oxidative stress by modulating the alterations of antioxidant status: GSH content, SOD, CAT activities, and LPO levels. These observations are again in line with a previous study in which Van modulated maneb-induced oxidative stress in Swiss albino mice 37 . In the present study, the Van-mediated inhibition in ROS generation may be attributed to its free radical scavenging property 38 .…”
Section: Discussionsupporting
confidence: 93%
“…Our in vivo results from the mice model also reflect that Van treatment significantly alleviated the MPTP-induced oxidative stress by modulating the alterations of antioxidant status: GSH content, SOD, CAT activities, and LPO levels. These observations are again in line with a previous study in which Van modulated maneb-induced oxidative stress in Swiss albino mice 37 . In the present study, the Van-mediated inhibition in ROS generation may be attributed to its free radical scavenging property 38 .…”
Section: Discussionsupporting
confidence: 93%
“…The antioxidant activity of vanillin observed in this study is consistent with other studies that postulated antioxidant and anti‐oxidative stress properties for this flavoring compound (Sefi et al., 2019; Tai et al., 2011).…”
Section: Discussionsupporting
confidence: 92%
“…It was shown that the addition of 0.01%-0.5% of vanillin helped keep intact the quality of cereal flakes that were precooked and dried. In addition to the flavor properties, vanillin has a protective function against oxidative stress (Sefi et al, 2019). The wood smoke is commonly used smoke flavorings and preservation methods for the curing of foods like sausages, ham, fish, bacon, and cheese (Bortolomeazzi, Sebastianutto, Toniolo, & Pizzariello, 2007).…”
Section: As Flavoring Agent In Foodsmentioning
confidence: 99%